# Web_Answers_2 - Unit 2 Problem Solutions 2.1 2.2 (a) See...

This preview shows pages 1–2. Sign up to view the full content.

(A + B + C + D) (A + B + C + E) (A + B + C + F) = A + B + C + DEF Apply second distributive law (Th. 8D) twice See FLD p. 626 for solution. 2.1 Unit 2 Problem Solutions 2.2 (a) In both cases, if X = 0, the transmission is 0, and if X = 1, the transmission is 1. 2.2 (b) In both cases, if X = 0, the transmission is YZ, and if X = 1, the transmission is 1. For the answer to 2.3, refer to FLD p. 626 2.3 F = [(A· 1 ) + (A· 1 )] + E + BCD = A + E + BCD 2.4 (a) Y = (AB' + (AB + B)) B + A = (AB' + B) B + A = (A + B) B + A = AB + B + A = A + B 2.4 (b) (A + B) (C + B) (D' + B) (ACD' + E) = (AC + B) (D' + B) (ACD' + E) By Th. 8D = (ACD' + B) (ACD' + E) By Th. 8D = ACD' + BE By Th. 8D 2.5 (a) (A' + B + C') (A' + C' + D) (B' + D') = (A' + C' + BD) (B' + D') {By Th. 8D with X = A' + C' } = A'B' + B'C' + B'BD + A'D' + C'D' + BDD' = A'B' + A'D' + C'B' + C'D' 2.5 (b) AB + C'D' = (AB + C') (AB + D') = (A + C') (B + C') (A + D') (B + D') 2.6 (a) WX + WY'X + ZYX = X(W + WY' + ZY) = X(W + ZY) {By Th. 10}

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 09/03/2008 for the course EE 316 taught by Professor Brown during the Fall '08 term at University of Texas at Austin.

### Page1 / 2

Web_Answers_2 - Unit 2 Problem Solutions 2.1 2.2 (a) See...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online